The problem elephants of Kaele: a challenge for elephant conservation in northern Cameroon - Martin Tchamba (Pachyderm)
Describes human-elephant conflict northern Cameroon's Kaele area located south of Maroua and fairly close to the Chadian border. Here a small resident population has recently been augmented by animals which have come into the area because of disruptive situations within their home territory in Chad. Outlines the need for research into the background of the elephants, strategies for mitigating human-elephants conflict situations and application of long term management programmes.